(untitled) (Medical Forum Monthly, 2024)
Objective: To compare the perceived factors influencing the idealized body image among medical and non-medical students in Peshawar Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the two Universities and a Medical College in Peshawar August 2018 to October 2018. Materials and Methods: Using Convenient sampling techniques, a total of 422 of medical and non-medical students were approached to be part of the study. The students during their break time were requested to take part in the study. Data Collection was based on indigenous questionnaire, coded and entered into SPSS version 20 and analyzed for descriptive statistics. Results: Result of the study indicated that out of 422 students 50.7% were non-medical and 49.3% were medical. Most of them were very conscious about their body image. Regarding body weight, 133(63.9%) of medical students perceived that they have normal body weight as compare to 120 (56.1%) non-medical students. However 43(20.1%) of non-medical student considered themselves as underweight as compared to 17(8.2%) of medical students which shows a significant difference (p=0.002). Student, regardless of their field of studyoften compared themselves with one or another perceived idealized person for body image. However, most (82.2% medical and 87.4% non-medical) of them were satisfied with their body image. There was no significant (p.0.05) difference regarding factors influencing the perceptions of medical and non-medical students about body image. Nearly 26% of the students were of the view that representation of females in media is a healthy trend which needs to be followed.In relationship to body weight and self-esteem, 30(14.4%) and 42(19.6%) of medical and non-medical students respectively were of the views that body weight has negatively affected their self-esteem indicating that students have similar impression regardless of their field of study (p=0.29). Conclusion: There is no significant difference in the perceptions of medical and non-medical students regarding idealized body image and its associated influencing factors, however, in comparison to medical students, a greater proportion of non-medical students of students considered themselvesas underweight.